Pengaruh Kualitas Pelayanan dan Lokasi terhadap Kepuasan Konsumen di Ende Laundry - Alya Junieta Dwiyana; Farid Pirdaus; Giska Wafiq Azizah Setiawan; Ogin Herdiana; Stephani Tri Nopelit; Zharifa Putri Azzahra (Lembaga Pengembangan Kinerja Dosen, 2025)
Customer satisfaction serves as a principal metric in evaluating the efficacy of a business, particularly within the service sector, exemplified by laundry services. Although service quality and business location are frequently regarded as determinants of satisfaction levels, prior studies indicate that their impact may vary based on the specific type and characteristics of the enterprise. Accordingly, this research seeks to investigate the degree to which service quality and location influence customer satisfaction at Ende Laundry. A quantitative methodology was employed, incorporating 50 customers selected via purposive sampling. A questionnaire employing a Likert scale was utilized as the primary instrument for data collection, with subsequent analysis performed using multiple linear regression, encompassing validity testing, reliability assessment, classical assumptions, and both partial and simultaneous tests. The results demonstrate that service quality significantly affects customer satisfaction, whereas location exhibits no substantial influence in a partial context. Collectively, these two variables account for 72.6% of the variance in customer satisfaction. The findings of this study indicate that service quality is the predominant determinant of customer satisfaction at Ende Laundry, whereas the influence of location appears to be comparatively limited. Consequently, it is advisable for management to prioritize enhancements in service quality through staff training and strategic location adjustments to bolster the customer experience.